FATIGUE RELIABILITY ANALYSIS OF WELDED JOINT BY USING FRACTURE MECHANICS APPROACH - Dwiputra Nanjaya, Melki
This thesis presents a fatigue reliability analysis of welded joint by using fracture mechanics approach. Numerically analysis was focused on a transverse-stiffener to bottom flange welded joint of a typical steel bridge. Crack growth model is based on the principles of fracture mechanics theory, while reliability analysis is performed by using Monte Carlo Simulation. Crack propagation rate analysis shows that crack growth model has a good accuration compared to the experiment results that has been done. Fatigue reliability analysis also compared to FORM (First Order Reliability Method) analysis that has been done by Mladen Lukic (Probabilistic Assesment of Welded Joint Versus Fatigue dan Fracture). Comparation shows that there is a diferrence in service time to get the same ? value (reliability index).